Literaturdidaktische Reflexionen zum Umgang mit visueller Narration am Beispiel von Nora Krugs Graphic Novel Heimat – Ein deutsches Familienalbum - Jeleč, Marijana; Kunecki, Luna (70 Jahre Germanistik in Zadar: Rückblicke, Einblicke, Ausblicke, 2026)
The visual articulation of complex topics and the dynamic interplay between text and image in graphic literature can facilitate young readers’ access to literature. This underscores its didactic value which lies in its ability to foster active, creative, and production-oriented learning. This article positions Nora Krug’s Heimat – Ein deutsches Familienalbum at the intersection of literary studies and literature didactics. It examines how visual storytelling opens pathways to literary and cultural topics in the classroom and argues for a stronger integration of graphic literature into educational practice. The paper explores how its multimodal structure of Heimat can help students to reflect on questions of identity, belonging, and historical responsibility. It further outlines approaches for creative and productive learning processes, demonstrating the potential of graphic novels in action- and production-oriented teaching. Finally, the article proposes didactic and methodological strategies that respond to contemporary reading habits and support key competencies such as critical media literacy, cultural memory awareness, empathy, communication, and creative-aesthetic expression. The discussion draws on theoretical perspectives by Eder (2016), Reid (2010), Bucher and Manning (2004), Eisner (2006), Hallet (2012), Rippl (2014), Kuzminykh (2014), and Lovrić (2019).